ECONOMIC EFFECTS OF AQUACULTURE SOCIETY THE SWALLOWS NEST IN DISTRICT OF LENGAYANG PESISIR SELATAN REGION - -, Mimi - (STKIP PGRI Sumbar, 2014)
This study aimed to obtain information, analyze and discuss data on the Economic Effects ofAquaculture Societies Swallows Nest In District of Lengayang Pesisir Selatan Region.This type of research is descriptive correlational. The study population was all swiftlet nestfarming owners who live in the District of Lengayang Pesisir Selatan Region totaling 72 people. Thesample in this study were taken with a total sampling ie 72 people who cultivated birds nest.Based on a simple linear regression analysis, the double (multiple) and the correlation it can beconcluded as follows: (1) There is the influence of capital Raising Swallows Nest in of DistrictLengayang Pesisir Selatan Region since tcount> t table (6.317> 1.663), the strength of strong ties (r =0.603) and the contribution of capital to the Swallows Nest Cultivation in District of LengayangPesisir Selatan Region includes a small (36.3%), (2) Means of Cultivation influences of SwallowsNest in the District of Lengayang Pesisir Selatan Region because tcount> t table (2.490> 1.663), themagnitude of the effect of including the low category (r = 0.285) and a very small contribution(8.1%), (3) There is the influence of income on the Cultivation of the Swallows Nest in the Districtof Lengayang Pesisir Selatan Region because tcount> t table (2.691> 1.663), the magnitude of theeffect is low (r = 0.306) and a very small contribution (9.4%) and (4) the influences of capital andrevenue Means together to Raising Swallows Nest in the District of Lengayang Pesisir SelatanRegion because F count> F table (15.712> 2.773), the magnitude of the effect of three variables onbird nest farming including strong (r = 0.633), whereas the contribution, including quite large(40.1%)